Fire & ash - Maberry, Jonathan (London : Simon and Schuster, 2013)
When Benny and his friends learn that a scientist may have discovered a cure for the zombie plague, they mount a search and rescue mission, unaware that the reapers want the cure to wipe humanity off the face of the earth.
Ages 12 up.
Keywords: Survival -- Juvenile fiction; Zombies -- Juvenile fiction